2007
DOI: 10.1161/circresaha.107.158915
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Regulation by N G , N G -Dimethylarginine Dimethylaminohydrolase of Rat Serum Asymmetric Dimethylarginine and Vascular Endothelium-Derived Relaxing Factor/NO

Abstract: Abstract-Asymmetric dimethylarginine (ADMA), which inhibits NO synthase, is inactivated by N G ,N G -dimethylarginine dimethylaminohydrolase (DDAH). We tested whether DDAH-1 or -2 regulates serum ADMA (S ADMA ) and/or endothelium-derived relaxing factor (EDRF)/NO. Small inhibitory (si)RNAs targeting DDAH-1 or -2, or an siRNA control were given intravenously to rats. After 72 hours, EDRF/NO was assessed from acetylcholine-induced, NO synthase-dependent relaxation and 4-amino-5-methylamino-2Ј,7Ј-diflouroflouresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
135
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 27 publications
9
135
2
2
Order By: Relevance
“…Similar to our study, these authors noted less vascular oxidative stress in TG versus WT mice following ANG II infusion (13). The effect of a DDAH2 transgene on vascular hypertrophy in the study by Hasegawa et al (13) may be explained by the recent observation that the DDAH2 isoen- zyme plays a greater role for ADMA metabolism in vascular tissue, whereas DDAH1 has a more pronounced effect on serum ADMA levels (39). This may explain the more pronounced effect of DDAH1 (in our study) versus DDAH2 (13) overexpression on systemic ADMA levels compared with WT littermates (37% vs. 26% decrease).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, these authors noted less vascular oxidative stress in TG versus WT mice following ANG II infusion (13). The effect of a DDAH2 transgene on vascular hypertrophy in the study by Hasegawa et al (13) may be explained by the recent observation that the DDAH2 isoen- zyme plays a greater role for ADMA metabolism in vascular tissue, whereas DDAH1 has a more pronounced effect on serum ADMA levels (39). This may explain the more pronounced effect of DDAH1 (in our study) versus DDAH2 (13) overexpression on systemic ADMA levels compared with WT littermates (37% vs. 26% decrease).…”
Section: Discussionsupporting
confidence: 89%
“…9,22 Using gene silencing techniques, disruption of DDAH1 gene activity induced a 50% increase in ADMA levels, while similar silencing of DDAH2 did not have any effects. 23 These data were supported by another laboratory. 9 Plasma and tissue ADMA and l-NMMA levels in DDAH1 knock-out mice were several folds higher than in wild-type mice.…”
Section: Genetic Variation In the Ddah Genes And Adma Levelsmentioning
confidence: 55%
“…Conversely, in vivo DDAH-2 gene silencing had no effect on plasma ADMA but reduced endothelium-dependent relaxation by 40% (11). These latter findings are particularly intriguing and demonstrate that elevated plasma ADMA is not associated with impaired endothelium-dependent relaxation, whereas loss of DDAH-2 activity is associated with impaired endothelium-dependent relaxation, despite the fact the plasma ADMA levels are not increased (11). These findings are further supported by a recent study demonstrating that down-regulation of DDAH-2 in response to hyperhomocysteinemia was not associated with increased plasma ADMA (25).…”
mentioning
confidence: 91%
“…Other laboratories have demonstrated that DDAH overexpression inhibits ADMA-mediated endothelial function in cerebral arteries and can enhance insulin sensitivity through modulation of nitric oxide (23,24). Using in vivo siRNA techniques, Wang et al (11) demonstrated that DDAH-1 gene silencing increased plasma levels of ADMA by 50%, but this increase had no effect on endothelium-dependent relaxation. Conversely, in vivo DDAH-2 gene silencing had no effect on plasma ADMA but reduced endothelium-dependent relaxation by 40% (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation